Social determinants of health and all-cause or cardiovascular mortality on osteoarthritis adults in the USA: a national cohort study - Xiong, Ruliu; Zhou, Xingmao (Frontiers in Public Health, 2025)
BackgroundSocial determinants of health (SDoH) are regarded as the fundamental causes of health and disease. Nevertheless, the relationship between SDoH and mortality risk in osteoarthritis (OA) patients remains poorly understood. This study aims to examine the associations between SDoH and all-cause or cardiovascular mortality risks among OA patients.MethodsAnalysis of data from ten National Health and Nutrition Examination Survey (NHANES) cycles (1999–2018) encompassing 4,681 OA participants was conducted. Multivariable Cox proportional hazards models and Kaplan–Meier survival analyses were employed to assess the associations between SDoH and mortality outcomes, encompassing all-cause mortality and cardiovascular mortality. Restricted cubic spline (RCS) modeling was employed to assess potential non-linear associations. Subgroup analyses and interaction evaluations were subsequently performed to investigate the consistency of the observed associations across predefined demographic and clinical subgroups.ResultsOver a median follow-up of 84 months, 1,300 participants died, including 447 cardiovascular deaths. In the fully adjusted multivariable model, Cox proportional hazards models showed that each 1-point increase in the cumulative SDoH score are associated with a 15% increased risk of all-cause mortality (HR = 1.15, 95% CI: 1.11–1.19) and a 13% elevated risk of cardiovascular mortality (HR = 1.13, 95% CI: 1.06–1.21). Most notably, Individuals with ≥5 adverse SDoH factors had a 119% higher risk of all-cause mortality (HR = 2.19, 95% CI: 1.72–2.79) and a 109% greater risk of cardiovascular mortality (HR = 2.09, 95% CI: 1.30–3.37) compared to those without any adverse factors. Kaplan–Meier survival curves further indicated significantly worse cumulative survival in high SDoH burden groups (Log-rank p < 0.001). Moreover, RCS analyses confirmed a linear dose–response gradient for SDoH levels and mortality risk (Non-linearity p > 0.05). Subgroup analyses identified stronger SDoH to all-cause mortality associations in low-BMI participants than high-BMI counterparts (Interaction p = 0.034).ConclusionAmong US adults with OA, adverse SDoH are associated with increased risks of all-cause mortality and cardiovascular mortality. Developing and implementing innovative public health approaches aimed at SDoH is crucial for mitigating premature mortality and addressing health inequities in this population. Integrating SDoH assessment into OA clinical management pathways and public health programs may improve prognostic outcomes; however, future research should validate these findings through large-scale prospective cohort studies and intervention trials.